2019
DOI: 10.1055/s-0039-3400842
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction in the Multiple Ligament Injured Knee

Abstract: Multiple ligament knee injuries are complex and can result from sports injuries or high energy trauma. The proper diagnosis and treatment of multiple ligament knee injuries are essential, and careful evaluation and planning are required to achieve successful outcomes. Anterior cruciate ligament (ACL) reconstruction in the multiple ligament injured knee is complicated by several factors, necessitating additional technical considerations. Patient selection, surgical timing, graft selection, and surgical techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…For knee surgeons, how many structures are injured, and which structures are injured are key issues for determining the strategy for the graft selection, the surgical procedure, xation devices, xation order. Marx et al reported that preoperative planning is critical, and the order of tunnels, graft passage, and xation should be decided prior to surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…For knee surgeons, how many structures are injured, and which structures are injured are key issues for determining the strategy for the graft selection, the surgical procedure, xation devices, xation order. Marx et al reported that preoperative planning is critical, and the order of tunnels, graft passage, and xation should be decided prior to surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the options of graft sources for knee ligament reconstruction are allografts, artificial ligaments, and autogenous grafts such as the semitendinosus tendon, gracilis tendon, bone-patellar tendon-bone, quadriceps tendon, and so on. [5][6][7][8][9] Unfortunately, allografts are not easily available in some countries, including Japan. Therefore, in these countries, graft selection and allocation are one of the major problems for MLKI surgery.…”
mentioning
confidence: 99%